Pengaruh Aplikasi Pupuk NPK Terhadap Pertumbuhan dan Produksi Tanaman Wortel (Daucus carota L.) - Giawa, Yunus Yaaro; Zulfida, Ida; Harahap, Lutfi Henderlan (JURNAL AGROPLASMA, 2024)
Indonesia is one of the tropical countries that has a variety of plants including vegetables and fruits. One that has the largest production is carrots (Daucus carota L.). Carrots are a type of shrub-shaped vegetable plant, which grows upright with a height of 30-100 cm or more. Carrots (Daucus carota L.) are a tuberous vegetable type plant that is usually reddish yellow or yellowish orange with a wood-like texture. The edible part of a carrot is the bulb or root. The plant stores food reserves in the bulb. The stem is short, has a taproot that changes its shape and function into a round and elongated tuber. The skin of carrot bulbs is thin and if eaten raw, it feels crunchy and slightly sweet. Here's a picture of a carrot plant. One way to increase the yield of carrot plants is by increasing soil productivity, using the addition of NPK fertilizer. This study used a factorial randomized group design (RAK). For accuracy in this study, it was repeated 3 times. namely: NPK fertilizer (N) with 3 levels, namely: N0 = Control, N1 = 15 g/plot, and N2 = 25 g/plot. From the ANOVA test results, the variance of treatments that have a significant effect is continued with the Duncan DMRT test at the 5% level. The results of the ANOVA test showed that the effect of NPK fertilizer treatment on plant height 21 hst and 28 hst, the number of leaves had no significant effect, but the observation of the diameter of the base of the tuber, the fresh weight of the plant per sample and the fresh weight of the plant per plot had a significant effect.  Keywords: NPK fertilizer, NPK dosage, and carrot plants